Analysis on the Types and Translation Procedures of English Metaphors into Indonesian in "The Sky is Falling" - Simanjuntak, Mariati (JET (Journal of English Teaching), 2017)
The aims of this research are to find the types of metaphors and the translation procedures used in translating the metaphors in the novel The Sky is Falling by Sidney Sheldon. This research used qualitative approach, and the data were taken from the novel The Sky is Falling by Sydney Sheldon, and its Indonesian version Langit Runtuh, translated by Hidayat Saleh. The main instruments of this research were the researcher herself, and the data sheets which contained the types of metaphors and the translation procedures applied. To achieve trustworthiness, the data has been checked by experts. The results of the research show that there are four types of metaphors found in the novel. They are cliche metaphors (5 data or 12.82%), adapted metaphors (5 data or 12.82%), stock/standard metaphors (11 data or 28.20%), and original metaphors (18 data or 46.16%). There are also four translation procedures applied, namely, replacing SL image with standard TL image (2 data or 5.13%), translation of metaphor by simile retaining the image (5 data or 12.82%), conversion of metaphor to sense (7 data or 17.95%), and reproducing the same image in the TL (25 data or 64.10%). Original metaphors are the mostly used metaphors in this novel possibly because the writer can describe events, objects, or situations in his novel more effectively by creating his own metaphors. The procedure of reproducing the same image in the TL is the one mostly applied because it provides the best translation possible to convey the message from the SL while still maintaining the context of the SL.